Implementasi Metode Rapid Applications Development Pengembangan Sistem Informasi Geografis Data Lansia - Akram, Muh. Saiful; Zaen, Mohammad Taufan Asri; Fahmi, Hairul (Journal of Information System Research (JOSH), 2025)
Elderly individuals experience comprehensive changes, biologically, physically, psychologically, and socially, as they age. At the Central Lombok Regency Social Service, administrators still face challenges in managing elderly data, particularly in collection and monitoring, due to limited access to the verification application, which can only be used during working hours. This study aims to develop a Geographic Information System (GIS) for the Elderly through a rapid and iterative development approach that is adaptive to user needs. The development focus is directed at administrators and officers, using the Rapid Application Development (RAD) method, which supports rapid and collaborative application development. The results of the black-box trial showed that all features functioned well and the system can be used to monitor the distribution of elderly data through map visualization on the dashboard feature, as well as to manage and map elderly information based on location coordinates in the elderly feature.